Konserwatyzm czy rewolucja? Próba klasyfikacji ideowej środowiska „Buntu Młodych” i „Polityki” (1931–1939) - Zakrzewski, Maciej (Pamięć i Sprawiedliwość, 2017)
The article describes the main points of political thinking of writers focused around “Bunt Młodych” (Rebel of the Young) – from 1937 called “Polityka” (Politics) magazine. In the 30s, when many of radical ideas were very popular, such authors as Adolf Bocheński, Aleksander Bocheński, Kazimierz Studentowicz or Ksawery Pruszyński tried to reform traditional conservative doctrine. Like many German or French conservative authors of that time, they were going to express traditional ideas in modern, in some way revolutionary, language. They constructed Polish version of imperial theorywhich connected geopolitical ideas of partition of Soviet Union (in cooperation with Third Reich) and modernization of Polish society and state. „The Rebel of the Young” Circle combined the intellectual achievement polish conservative thinkers as Michał Bobrzyński or Stanisław Koźmian with Stanisław Brzozowski’s thought who was one of the most important socialist thinker. In this way Jerzy Giedroyc (editor of the magazines) and his cooperators made an unique political doctrine that we could classify as form of conservative revolution.